Integrated Pharmacological and Pharmacokinetic Assessment of Gymnema sylvestre as an Adjunct to Glimepiride Therapy in Diabetes” - kumar, Ashwani; Sharma, Hariom; Kukkar, Rajiv (Journal of Neonatal Surgery, 2025)
The present study investigated the pharmacodynamic and pharmacokinetic interactions between Gymnema sylvestre aqueous extract and glimepiride in streptozotocin (STZ)-induced diabetic rats. Phytochemical analysis confirmed the presence of flavonoids, saponins, tannins, glycosides, alkaloids, and phenolic compounds, with quercetin identified as a major bioactive constituent by HPTLC. In vitro studies demonstrated dose-dependent inhibition of hepatic CYP3A activity by the extract, indicating potential herb drug interaction. In vivo, G. sylvestre extract produced significant, dose-dependent reductions in blood glucose levels and improved oral glucose tolerance, comparable to glimepiride. The extract also restored antioxidant enzymes (SOD, CAT, and GSH), reduced lipid peroxidation, and normalized elevated liver enzymes (AST and ALT), indicating strong antioxidant and hepatoprotective effects. Combination therapy with glimepiride further enhanced antihyperglycemic and protective outcomes. Pharmacokinetic evaluation revealed altered glimepiride disposition in the presence of the extract, with reductions in Cmax, AUC, and half-life. These findings suggest that Gymnema sylvestre is a promising adjunct in diabetes management, though careful consideration of herb–drug interactions is required..